What Lies Between - Thomson, Graeme; Maglioni, Silvia (Re-visiones, 2024)
The present text establishes a narrative of the filmmaking process by the authors of Facts of life. A film developed with 18 hours of video from Gilles Deleuze’s courses at the University of Vincennes (1975-76). A working material taped by Marielle Burkhalter as part of her Master Project "film thoght in its becoming".